L-Tryptophan Measurement using Spectrophotometry and Spectrofluorometry in Pharmaceutical Formulations Containing 1-Chloro-4 Nitrobenzofurazon - Madri, Mohammed Sahib; Hussein, Omar Saleh (American Journal of Bioscience and Clinical Integrity, 2025)
For detecting L-tryptophan in pharmaceutical formulations, a novel, simple, and extremely accurate spectrophotometric and spectrofluorometric approach has been developed and shown to be successful. The production of an orange-colored molecule that absorbs at a wavelength of 405 nanometers when L-tryptophan and 1-chloro-4-nitrobenzofurazan (NBF-Cl) react in an alkaline medium (pH 10.5) served as the foundation for the spectrophotometric and fluorometric procedures. The variables affecting L-tryptophan’s reaction to NBF were carefully investigated and improved. Under optimal reaction conditions, good linear correlations between the readings and the L-tryptophan concentrations in the range of 12 to 60 µg /mL were found. 8.6 and 2.85 µg/mL were found to be the limits of quantitation (LOQ) and detection (LOD), respectively. This method proved successful in identifying L-tryptophan in its pharmacological forms.